(untitled) (Itinera, 2024)
Widely dealt with in its use in the horror film genre that best suits it, disgust has not found yet a theoretical framework as an aesthetic instrument in the sphere of more experimental cinema, which nonetheless boasts an intrinsic propensity for formal research which is useful to qualify an aesthetic category. Taken here as a case study in order to demonstrate the expressive potential overshadowed by the mainstream scene, Stan Brakhage’s The Act of Seeing with One’s Own Eyes stands out for the original aesthetic function assigned to disgust: to impose iconism as a semiotic regime of the film. This paper would like to articulate the theoretical path from disgust to iconism, as well as the theoretical-aesthetic effects resulting from it. In the first instance, the contrasting positions on the sublime of Kant and Burke are considered. Having admitted with the latter the materialist monism and the illusory character of the sensible, one can arrive at the sign regime sought by Brakhage by placing a third condition alongside the others two: Bataillean dépense. Hav- ing defined the causes, the paper moves on to describe the effects. The iconism of disgust is capable of transforming ontologically the status of Brakhage’s realization from work to operation. It is from such iconism that follows the inherent capacity of disgust to pierce the gaze: preventing it from signifying the image and forcing it before that from which it seeks shelter. The detachment – that is the poetic and maieutic center of the operation – imposed by disgust on its own subject, becomes fruitfully ambiguous: semantically re- versed, there is no longer detachment from the disgusting object, but rather from the stri- ated eye of epistemological prejudice. Through disgust, the distance between the specta- tor and the image is thus cancelled, placing it instead between the spectator and the gaze. Thus exorcised, Brakhage’s film can only be watched with those own eyes indicated by the title.